Conflicting and complementary notions of responsibility in caregiver’s and health care workers’ vaccination narratives in the Philippines - Ulmido, Ma Leslie; Reñosa, Mark Donald; Wachinger, Jonas; Endoma, Vivienne; Landicho-Guevarra, Jhoys; Landicho, Jeniffer; Bravo, Thea Andrea; Aligato, Mila; McMahon-Rössle, Shannon A. (Journal of global health, 2024)
Vaccines are essential in the global fight against infectious diseases, as they are cost-effective and safe for preventing millions of deaths annually, particularly among young children [1]. However, recent declines in vaccination rates, often associated with increased vaccine hesitancy (VH), threaten decades of progress in reducing child mortality and morbidity. This decline has resulted in […]
Gesehen am 12.11.2024